Pengembangan bahan ajar teks eksplanasi melalui model pembelajaran cooperative learning untuk meningkatkan minat belajar siswa pada mata pelajaran PAI di SMA Negeri Siak Kecil Kabupaten Bengkalis - Astika, Yuni; Zein, Mas’ud; Zamsiswaya, Zamsiswaya (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This research is motivated by the less than optimal implementation of learning, which impacts students' low interest in studying. The purpose of this study is to develop teaching materials for explanatory texts through a cooperative learning model that is suitable and effective in increasing students' interest in learning in the subject of Islamic Education and Moral Education at State Senior High School 1 Siak Kecil, Bengkalis Regency. This type of research is research and development (R&D) using the ADDIE model. The results show that the developed teaching materials are very feasible to use, based on material expert validation results of 98.36% and media expert validation of 100%. The implementation of the cooperative learning model is carried out in four stages, namely: (1) preparation stage, including the provision of learning media; (2) initial stage, such as prayer, greetings, attendance, objectives, and group formation; (3) core stage, consisting of material delivery, group discussions, and presentations; as well as (4) the closing stage which includes assessment, reflection, awarding, and closing. This model has been proven to significantly increase students' interest in learning.